Correction: Cooper et al. A Retrospective Study Reviewing Timing to Onset of Habitual Psychogenic Non-Epileptic Seizures in a Home Video Telemetry Cohort. Brain Sci. 2024, 14, 1187 - Jade Cooper; Helen Chester; Arianna Fozzato; Elisaveta Sokolov (Brain Sciences)
In the original publication [...]